HUBUNGAN TINGKAT WORK-LIFE BALANCE TERHADAP TINGKATKEPUASAN KERJA KARYAWAN ORGANISASI PELAYANANKEMANUSIAAN, KARYAWAN YAYASAN PLAN INTERNATIONALINDONESIA - Larasati, Iga; Rahayu, Ety (UI Scholars Hub, 2019)
This undergraduate thesis discusses about the correlation of work-life balance to job satisfaction among Yayasan Plan International Indonesia’s Employees. This research is a quantitative research with descriptive design. This research is background by the importance of employee’s satisfaction in the Human Service Organization’s setting. Meanwhile, the research about employee’s job satisfaction among Human Service Organization is still rare. The result of this research shows that there’s a very weak correlation between the level work-life balance to the level of job satisfaction among Yayasan Plan International Indonesia’s Employees. This can be caused by the difference in characteristic between HSO and company. Job satisfaction in HSO may not always be correlated with the level of work-life balance. It can be correlated with its characteristic, people as a raw material, unclear and problematic organizatinons goals, uncertainty in determining service technology, and intensive interaction between employee and client as one of core activities in HSO